2016
DOI: 10.1111/geoa.12140
|View full text |Cite
|
Sign up to set email alerts
|

Trace element distribution and implications in sediments across the allerød–younger dryas boundary in the netherlands and belgium

Abstract: In the Northern Hemisphere, the Younger Dryas cooling occurred between 12.8 and 11.7 ka bp. This cooling is thought to have been the result of an abrupt change in atmospheric and oceanic circulations. One of the hypotheses explaining such a change suggests that just before the onset of the Younger Dryas cooling, multiple airbursts/impacts occurred over the Northern Hemisphere. We studied the late Pleistocene sediments from the Netherlands and Belgium to check whether a sudden short event might have taken place… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 76 publications
0
10
0
Order By: Relevance
“…In 2013, Petaev et al reported the discovery of a distinct peak concentration in Pt in the GISP2 core of Greenland in the YD peak, which they attributed to material deposited by a Pt-rich impactor. Subsequently Pt enrichment well above background levels in YDB sediments have been reported at 28 sites across North America, Europe, and Asia by Moore et al (2017) and Gramly et al (2017); Andronikov and Andronikova (2016) and Andronikov et al (2011, 2014, 2015, 2016b, 2016c) also reported peak concentrations of Ir in the YDB layer at multiple sites in North America and Europe.…”
Section: Iridium and Platinum And Their Interpretationmentioning
confidence: 70%
“…In 2013, Petaev et al reported the discovery of a distinct peak concentration in Pt in the GISP2 core of Greenland in the YD peak, which they attributed to material deposited by a Pt-rich impactor. Subsequently Pt enrichment well above background levels in YDB sediments have been reported at 28 sites across North America, Europe, and Asia by Moore et al (2017) and Gramly et al (2017); Andronikov and Andronikova (2016) and Andronikov et al (2011, 2014, 2015, 2016b, 2016c) also reported peak concentrations of Ir in the YDB layer at multiple sites in North America and Europe.…”
Section: Iridium and Platinum And Their Interpretationmentioning
confidence: 70%
“…This resolution is much higher than nearly all terrestrial YDB stratigraphic sequences. Pt-rich sediment and Pt-rich spherules have also been reported in YDB-age sediment (Andronikov et al 2014(Andronikov et al , 2015(Andronikov et al , 2016a(Andronikov et al , 2016b; Andronikov and Andronikova 2016; Moore et al 2017; see "Widespread YDB Platinum Deposition" in the appendix).…”
Section: Resultsmentioning
confidence: 88%
“…Their results indicate that extraterrestrial Pt settled out of the atmosphere into a 21-y interval of ice, rising 100 times above background at 12,822 5 140 cal BP, within the range 12,836-12,815 cal BP. Including this discovery, there have been multiple independent reports of Pt abundance peaks in the YDB layer at 22 sites in North America, Europe, and Asia: one site in Greenland (Petaev et al 2013b), one site in Russia (Andronikov et al 2014), four sites in Lithuania (Andronikov et al 2015), one site on the French-Italian border (Mahaney et al 2016b), two sites in the Netherlands (Andronikov et al 2016b), one site in Belgium (Andronikov et al 2016b), and 12 sites in the United States (Andronikov and Andronikova 2016;Moore et al 2017).…”
Section: Resultsmentioning
confidence: 97%